It Is All Part of the Process: Becoming Pedagogical Through Artful Inquiry (LEARNing Landscapes, 2016)
The experiences and challenges that teacher-educators go through tend to be private and go unnoticed (Berry & Loughran, 2005). Through self-study, teacher-educators can re ect on their practices and learn from each other’s practices. As a novice teacher- educator who was teaching an inquiry-based teaching science methods class with a collaborative teaching team, I explore my experience of being a teacher-educator through arts-based self-study. In this paper, I discuss how the process of artful inquiry informed my own research and teaching practices. Based on the idea of a/r/tography, I link my artistic, research, and teaching practices together to explore what it means to be becoming pedagogical (Gouzouasis, Irwin, Miles, & Gordon, 2013).
Keywords: teacher education; arts-based; self-study; a/r/tography; pedagogy